2013
DOI: 10.2478/s13382-013-0141-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between neck musculoskeletal complaints and work related factors among public service computer workers in Kaunas

Abstract: Objectives: Information technologies have been developing very rapidly, also in the case of occupational activities. Epide miological studies have shown that employees, who work with computers, are more likely to complain of musculoskeletal disorders (MSD). The aim of this study was to evaluate associations between neck MSD and individual and work related factors. Materials and Methods: The investigation which consisted of two parts -a questionnaire study (using Nordic Mus culoskeletal questionnaire and Copenh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
0
32
0
5
Order By: Relevance
“…Despite the fact that similar estimates for the European Union (EU) countries are not available, several crosssectional studies performed in Europe have reported a prevalence of 30-62% of musculoskeletal symptoms in the neck or shoulder region studies, and suggest that referred complaints would increase with age and working age, being more prevalent among women than men [4,[6][7][8][9][10][11][12]. However, as this same difference has been identified in the general working population, its causative association may be doubtful [13][14][15].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Despite the fact that similar estimates for the European Union (EU) countries are not available, several crosssectional studies performed in Europe have reported a prevalence of 30-62% of musculoskeletal symptoms in the neck or shoulder region studies, and suggest that referred complaints would increase with age and working age, being more prevalent among women than men [4,[6][7][8][9][10][11][12]. However, as this same difference has been identified in the general working population, its causative association may be doubtful [13][14][15].…”
Section: Introductionmentioning
confidence: 79%
“…Not coincidentally, are WMSDs, and particularly neck and back pain and upper-limb symptoms therefore interpreted as common health problems with a multifactorial aetiology, including mixed, prolonged and often ill-defined exposures over a long period of time [5][6][7][10][11]. Moreover, as a large number of epidemiological studies about WMSDs amongst VDU workers are based on self-referred symptoms, the lack of clinical evaluation data, the possible risk is the overreporting of musculoskeletal complaints inconsistently associated [1,8,[10][11][12][13]. Besides, studies about WMSDs often lack accurate evaluation of personal medical history, failing to refer to previous acute traumas or systemic diseases [13,21].…”
mentioning
confidence: 99%
“…No entanto, a postura sentada favorece a ocorrência de problemas na coluna, associados à fraqueza dos músculos abdominais e do tronco. Além disso, há associações de lesões musculoesqueléticas de pescoço com maior experiência de trabalho, alta sobrecarga muscular e exigências cognitivas sem pausas adequadas (KALINIENE et al 2013).…”
Section: Introductionunclassified
“…Vale ressaltar que as intervenções ergonômicas devem ser implementadas de acordo com as necessidades de cada trabalhador, levando em consideração os fatores biomecânicos e organizacionais (GONÇALVES, 1995;KALINIENE et al, 2013).…”
Section: Introductionunclassified
“…Finally, Kaliniene et al [216] collected data using the NMQ, the Copenhagen psychosocial questionnaire, and RULA for workers in three companies in the public sector who used a computer. The results confirmed that the neck disorders were associated with individual factors and with the work conditions, calling for ergonomic improvements.…”
Section: Computer Usersmentioning
confidence: 99%